Genome-wide and locus specific alterations in CDC73/HRPT2-mutated parathyroid tumors. - Luqman Sulaiman (Public Library of Science (PLoS), 2012)
Mutations in the hyperparathyroidism type 2 (HRPT2/CDC73) gene and alterations in the parafibromin protein have been established in the majority of parathyroid carcinomas and in subsets of parathyroid adenomas. While it is known that CDC73-mutated parathyroid tumors display specific gene expression changes compared to CDC73 wild-type cases, the molecular cytogenetic profile in CDC73-mutated cases compared to unselected adenomas (with an expected very low frequency of CDC73 mutations) remains unknown. For this purpose, nine parathyroid tumors with established CDC73 gene inactivating mutations (three carcinomas, one atypical adenoma and five adenomas) were analyzed for copy number alterations and loss of heterozygosity using array-comparative genomic hybridization (a-CGH) and single nucleotide polymorphism (SNP) microarrays, respectively. Furthermore, CDC73 gene promoter methylation levels were assessed using bisulfite Pyrosequencing. The panel included seven tumors with single mutation and three with double mutations of the CDC73 gene. The carcinomas displayed copy number alterations in agreement with previous studies, whereas the CDC73-mutated adenomas did not display the same pattern of alterations at loci frequently deleted in unselected parathyroid tumors. Furthermore, gross losses of chromosomal material at 1p and 13 were significantly (p = 0.012) associated with parathyroid carcinomas as opposed to adenomas. Quantitative PCR-based copy number loss regarding CDC73 was observed in three adenomas, while all the carcinomas were diploid or showed copy number gain for CDC73 gene. Hypermethylation of the CDC73 gene promoter was not observed. Our data could suggest that CDC73-mutated parathyroid adenomas exhibit a partly unique cytogenetic profile in addition to that of carcinomas and unselected adenomas. Furthermore, CDC73-mutated carcinomas displayed losses at 1p and 13 which are not seen in CDC73-mutated adenomas, making these regions of interest for further studies regarding malignant properties in tumors from CDC73-mutated cases. However, due to the small sample size, validation of the results in a larger cohort is warranted.